2020
DOI: 10.21203/rs.3.rs-112779/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Female Sex Work Targeted Community-based Interventions Along the HIV Treatment Cascade in Sub-Saharan Africa: A Systematic Review and Meta-analysis

Abstract: Background: Female Sex Workers are extremely vulnerable and highly susceptibility to being infected with human immunodeficiency virus. As a result, community based targeted interventions have been recommended as one of the models of care to improve access to HIV services and continued engagement in care. However little is known about the specific community intervention packages that have optimal effect on FSWs access and retention in HIV care. This paper synthesized evidence on the effectiveness of community-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…Findings from this scoping review on the effect of KP-CBART on outcomes along the HIV care continuum ranging from HIV testing to viral load suppression and retention in care including ART delivery, showed that outcomes in KP-CBART were at least as good as in facility-based care. Our conclusion is coherent with the conclusion from a recent review on CBART for FSW, even though most of the included studies did not overlap, as different inclusion criteria were used [ 13 ]. Our review only included studies for which ART delivery was part of the intervention, and studies in which KP had a role in KP-CBART delivery.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Findings from this scoping review on the effect of KP-CBART on outcomes along the HIV care continuum ranging from HIV testing to viral load suppression and retention in care including ART delivery, showed that outcomes in KP-CBART were at least as good as in facility-based care. Our conclusion is coherent with the conclusion from a recent review on CBART for FSW, even though most of the included studies did not overlap, as different inclusion criteria were used [ 13 ]. Our review only included studies for which ART delivery was part of the intervention, and studies in which KP had a role in KP-CBART delivery.…”
Section: Discussionsupporting
confidence: 89%
“…However, this review only focussed on FSW, included studies regardless of the level of involvement of FSW in care provision, and included studies regardless of whether ART was provided within the communities. Moreover, the modalities used for KP-CBART were not summarized [ 13 ]. In our review, we explored the effect of CBART along the continuum of HIV care on clinical outcomes among KP in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A trial and a prospective study in Tanzania showed high retention rates in ART care among FSW receiving ART through a community-based ART programme for Key populations (KP-CBART) [ 13 , 14 ] However, there are only few studies on how this evidence is translated to less-resourced routine care [ 9 , 15 ]. These studies reported retention rate in KP-CBART models between 6–12 months on ART.…”
Section: Introductionmentioning
confidence: 99%